Performance improvement of a hydraulic turbine generation system using adaptive fuzzy sliding mode control - Cho, Dae Hyun; Bak, Yeongsu; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2019)
This paper presents a performance improvement of a hydraulic turbine generation system using adaptive fuzzy sliding mode control. A dynamic response of current control on the part of generator should be improved to utilize differential pressure energy efficiently in hydraulic turbine generation system. Current ripple on the part of generator should be reduced in terms of noise and generator's life. Adaptive fuzzy sliding mode control scheme is applied to generator in order to improve the performance of a hydraulic turbine generation system. Sliding mode control is used to make the dynamic response improve and fuzzy logic is used to select a proper gain of sliding mode control to decrease chattering phenomenon in steady state. The effectiveness and performance of the proposed method for hydraulic turbine generation system are verified by simulation and experiment.
Keywords: Adaptive fuzzy sliding mode controls (AFSMC); Chattering phenomenon; Current ripples; Differential pressures; Generation systems; Steady state; Chattering phenomenon; Dynamic response; Fuzzy logic; Hydraulic turbine generation system; Sliding mode control